Lymphangioma of the fetal neck within the PIK3CA‐related‐overgrowth spectrum (PROS): A case report - Jann Lennard Scharf; Michael Gembicki; Christoph Dracopoulos; Yorck Hellenbroich; Anne Offermann; Guido Stichtenoth; Kianusch Tafazzoli‐Lari; Lars Tharun; Jan Weichert (Clinical Case Reports, 2021)
Abstract The delineation of the prenatal diagnostic key features of PIK3CA‐related overgrowth spectrum disorders will assume a crucial part in future and a prenatal diagnosis of the causing mutations would provide physicians with a simplified interdisciplinary perinatal management.